Social disputes over GMOs: an overview - Campos Motta, Renata (Sociology compass, 2014)
This review provides an overview of social research on genetically modified crops (GM crops), also known as genetically modified organisms (GMOs). Academic inquiry on the social disputes over the future of agriculture biotechnology has multiplied since the mid-1990s, when the first seeds were approved for market commercialization. This essay identifies and describes five prominent analytical approaches to explain public controversies over GMOs: the political economy of food and agriculture, social studies on science, democracy theory, research on corporations and hegemony, and social movement and peasant studies. This overview concludes by arguing that these different strains, although each privileging one analytical dimension and one level of analysis, converge in (i) the definition of the relevant explanatory factors, (ii) in the identification of the various levels of analysis - global, transnational, national and local - involved in the issue and (iii) in the prognostic that social disputes over GMOs are likely to remain a topic of public and scholar interest in the near future.